Chronic CNT Fiber Interface With Median Nerve at Acupoint PC6 for Rat’s Myocardial Ischemia Control - Aotian Yu; Pengwei Li; Junge Yuan; Lei Han; Meng Li; Xiaodan Song; Chang Liu; Qixuan Fu; Simin Ning; Yemao Chai; Yuanyuan Shang; Anyuan Cao; et al. (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Myocardial ischemia is one of the most prevalent cardiovascular diseases, underscoring the need for safer and effective therapeutic approaches. Peripheral nerve stimulation, particularly vagus nerve stimulation has emerged as a promising non-pharmaceutical therapy for managing myocardial ischemia. However, vagus nerve stimulation carries risks, such as off-target effects and adverse cardiac events due to its extensive innervation and mixed afferent/efferent fiber composition. Therefore, it is crucial to explore a safer and more user-friendly peripheral nerve interface. In this work, we developed a novel chronic median nerve interface using carbon nanotube fibers as electrodes to stimulate the median nerve at the acupoint PC6 for myocardial ischemia control. Carbon nanotube fibers exhibited excellent biocompatibility, flexibility, conductivity, and charge storage capacity, making them ideal for reliable and prolonged median nerve stimulation. Our results demonstrated that median nerve stimulation at the acupoint PC6 achieved therapeutic effects comparable to electroacupuncture, including improvement in S-T segment values, LF/HF ratios, cardiac index and cardiac troponin T, while being safer and easier to operate than vagus nerve stimulation. Moreover, median nerve stimulation exhibited superior transient and residual effects compared to electroacupuncture, despite a slower response time. Additionally, histological and fluorescence analyses confirmed the safety of the CNTF-based interface over time. These findings suggested that median nerve stimulation at the acupoint PC6 combined the efficacy of nerve stimulation with the safety of acupuncture, offering a promising approach for myocardial ischemia control, particularly in chronic and repeated treatment scenarios. Further researches are warranted to optimize CNTF properties, elucidate the underlying mechanisms of median nerve stimulation, and explore its potential in clinical applications.